If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4 = 10y + 36 Reorder the terms: -4 + 2y = 10y + 36 Reorder the terms: -4 + 2y = 36 + 10y Solving -4 + 2y = 36 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. -4 + 2y + -10y = 36 + 10y + -10y Combine like terms: 2y + -10y = -8y -4 + -8y = 36 + 10y + -10y Combine like terms: 10y + -10y = 0 -4 + -8y = 36 + 0 -4 + -8y = 36 Add '4' to each side of the equation. -4 + 4 + -8y = 36 + 4 Combine like terms: -4 + 4 = 0 0 + -8y = 36 + 4 -8y = 36 + 4 Combine like terms: 36 + 4 = 40 -8y = 40 Divide each side by '-8'. y = -5 Simplifying y = -5
| 4b-3=3b+9 | | 2(x^2+60x-200)=0 | | 14x+8=6x+12 | | 2x^5-32=0 | | 2(6x-4)=27 | | log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d | | cos(x)=-3.8 | | 3x-61= | | X^2-14x+17=-6x+2 | | 4(3x+6)=-38+2 | | -2tk=20 | | 6X+5X+9X=180 | | x-x^2=0.19 | | 8-(2z-9)=8-3z | | X^2+3x-24=4 | | 8x^5-196x^4+153x^3-4096x^2=0 | | 12x+1=11x+16 | | 6x-30=5(3+x) | | (X^2+5)+(x^2+4)= | | 9x-(3x+14)=16 | | 3000=(200+8x)(15-.50x) | | -12x+3+12x= | | B(b+4)=140 | | 25=48-3x | | 2p-3(2-2p)=3(p-4)-24 | | 15ab-12a= | | 6(2m-3)-3m-2m=18+m | | 5x+4=53-2x | | 9(x-4)=54 | | X+131=x+61 |